2022
DOI: 10.1186/s12888-022-04426-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high prebiotic and probiotic dietary education in the SARS-CoV-2 era: improved cardio-metabolic profile in schizophrenia spectrum disorders

Abstract: Background The development of new aetiological premises, such as the microbiota-gut-brain axis theory, evidences the influence of dietary and nutritional patterns on mental health, affecting the patient's quality of life in terms of physical and cardiovascular health. The aim was to determine the impact of a nutritional programme focused on increasing the intake of prebiotic and probiotic food on cardio-metabolic status in individuals with schizophrenia spectrum disorders in the contextual sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In particular, the consumption of raw materials with prebiotics (green leafy vegetables, high-fiber fruit, whole grains) improved the general cardio-metabolic profile in patients with schizophrenia spectrum disorders [31], while inulin, resistant starch, resistant maltodextrin, and rice bran played an active role in reducing the markers of inflammation (plasma zonulin and stool calprotectin), positively affected gut microbiota composition with an increase in SCFA, had a clinical impact leading to reduced severity of motor and non-motor Parkinson's disease symptoms and improved gastrointestinal function [32].…”
Section: Schizophrenia and Parkinsonmentioning
confidence: 99%
“…In particular, the consumption of raw materials with prebiotics (green leafy vegetables, high-fiber fruit, whole grains) improved the general cardio-metabolic profile in patients with schizophrenia spectrum disorders [31], while inulin, resistant starch, resistant maltodextrin, and rice bran played an active role in reducing the markers of inflammation (plasma zonulin and stool calprotectin), positively affected gut microbiota composition with an increase in SCFA, had a clinical impact leading to reduced severity of motor and non-motor Parkinson's disease symptoms and improved gastrointestinal function [32].…”
Section: Schizophrenia and Parkinsonmentioning
confidence: 99%
“…Huang et al, in their two trials on patients receiving olanzapine therapy at the first psychotic episode, showed that administering probiotics (Bifidobacteri, Lactobacilli, Enterococci) improved the metabolic profile of the patient and that the concomitant administration of dietary fiber helps prevent the weight gain expected when administering antipsychotic therapies such as olanzapine [44]. The other three studies on the effect of probiotics [49,53,55] showed an improvement in PANSS score [49,53] and metabolic profile [49,53,55]. In addition to probiotics, some of these studies included the concomitant administration of vitamin D [49], selenium [53], and prebiotics [55].…”
Section: Schizophreniamentioning
confidence: 99%
“…The other three studies on the effect of probiotics [49,53,55] showed an improvement in PANSS score [49,53] and metabolic profile [49,53,55]. In addition to probiotics, some of these studies included the concomitant administration of vitamin D [49], selenium [53], and prebiotics [55].…”
Section: Schizophreniamentioning
confidence: 99%
“…The reason for not including these data was that the main objective was to assess the intervention's efficacy in modifying this population's dietary patterns with such particular characteristics. However, readers interested in this type of information can consult a recent paper in which these results have been included [47].…”
Section: Limitationsmentioning
confidence: 99%